1994
DOI: 10.1007/bf01992043
|View full text |Cite
|
Sign up to set email alerts
|

Nematodes and the spleen: An immunological relationship

Abstract: Despite being a major organ of the immune system, the spleen's role in resisting, controlling or simply ameliorating nematode infections has been neglected. A review of both filarial and gastrointestinal nematodes suggests that though it is difficult to fully assess or quantify the organ's importance in vivo, the spleen is prominent in acting against nematode parasites in mammals. One manifestation of this is that transfer of lymphocytes from the spleen of immunised individuals can protect recipients against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…Having found that the female spleen is associated with nematodes as well as haemoprotozoa (John, 1993), it was necessaiy to see whether these correlations are independent. In the event, relative nematode presence is significantly associated with relative female spleen weight when also accounting for the numbers of birds infected with, and examined for, haematozoa (slope 0.38, F,,,,, = 8.68, lip = 25, P < 0.01); furthermore, significance is also retained when additionally partialling out the numbers of trematode-infected and cestodeinfected birds (slope 0.38, F,,,, = 8.64, np = 25, P < 0.01).…”
Section: Resuli'smentioning
confidence: 99%
See 3 more Smart Citations
“…Having found that the female spleen is associated with nematodes as well as haemoprotozoa (John, 1993), it was necessaiy to see whether these correlations are independent. In the event, relative nematode presence is significantly associated with relative female spleen weight when also accounting for the numbers of birds infected with, and examined for, haematozoa (slope 0.38, F,,,,, = 8.68, lip = 25, P < 0.01); furthermore, significance is also retained when additionally partialling out the numbers of trematode-infected and cestodeinfected birds (slope 0.38, F,,,, = 8.64, np = 25, P < 0.01).…”
Section: Resuli'smentioning
confidence: 99%
“…Acanthocephalans were not analysed because of infrequency of infection. Haematozoa prevalence data were obtained from Peirce (1981), primarily, andGreiner et al (1975) (see John, 1993).…”
Section: Data Parasitesmentioning
confidence: 99%
See 2 more Smart Citations
“…This organ is a major site for lymphocyte recirculation, presentation of antigens to T cells and activation of immune response (lymphocyte differentiation, antibody synthesis) (John 1994a). Moreover, this organ seems to be important in acting against nematode parasites in mammals and birds (John 1994b;Shutler et al 1999;Morand and Poulin 2000). We postulated that an individual host with a relatively larger spleen mounts a Fig.…”
Section: Immunocompetence Assessed By Spleen Sizementioning
confidence: 99%